Red Hat OpenShift deployment with IBM Storage Enabler for containers : version 1, release 1 (IBM Corporation, 2019)
IBM Storage for Red Hat OpenShift Container Platform is a comprehensive container-ready solution that includes all the hardware & software components necessary to setup and/or expand your Red Hat OpenShift Container Platform V3.11 environment. IBM Storage, bringing enterprise data services to containers. In this blueprint, learn how to: " Combine the benefits of IBM Systems with the performance of IBM Storage solutions so that you can deliver the right services to your clients today! " Build a 24 by 7 by 365 enterprise class private cloud with Red Hat OpenShift Container Platform " Leverage enterprise class services such as NVMe based flash performance, high data availability, and advanced container security IBM Storage for Red Hat OpenShift Container Platform: designed for your DevOps environment for on-premises deployment with easy-to-consume components built to perform and scale for your enterprise. Simplify your journey to cloud with pre-tested and validated blueprints engineered to enable rapid deployment and peace of mind as you move to a hybrid multicloud environment. You now have the capabilities